Infectious complications in liver transplanted patients - E. P. Khlebnikov; V. A. Kubyshkin; A. V. Chzhao (Трансплантология (Москва))
The use of novel technologies in surgery increases liver transplantation surgical activity. However, this does not reduce the incidence of postoperative infectious complications. The growing microbial resistance to antibiotics and the increasing role of fungi in the etiology of nosocomial infections remain to be a cause of purulent complications. In this connection it is urgent to study the causes of infectious complications during transplantation of the liver and other vital organs.